Sie sind auf Seite 1von 10

(1) Let f (z) be the principal branch of z 4i .

(a) Find f (i).


Solution. f (i) = exp(4i Log(i)) = exp(4i(/2)) = e2 .
(b) Show that
f (z1 )f (z2 ) = f (z1 z2 )
for all z1 , z2 6= 0, where = 1, e8 or e8 .
Proof. We have
f (z1 )f (z2 )
= exp(4i(Log z1 + Log z2 Log(z1 z2 )))
f (z1 z2 )
= exp(4i(Log z1 + Log z2 Log(z1 z2 )))
= exp(4(Arg z1 + Arg z2 Arg(z1 z2 ))) = exp(8n)
for some integer n. And since < Arg z1 , <
Arg z2 and < Arg(z1 z2 ) ,
3 < Arg z1 + Arg z2 Arg(z1 z2 ) < 3
and hence 3 < 2n < 3. So n = 1, 0 or 1. Correspondingly,
f (z1 )f (z2 ) = f (z1 z2 )
with = e8n = e8 , 1 or e8 .

(2) Let f (z) be an entire function satisfying


|f (z)| |z| + 1
for all z. Show that f (z) az + b for some constants a, b C
satisfying |a| 1 and |b| 1.
Proof. Since f (z) is entire,

X
f (n) (0) n
f (z) =
z
n!
n=0
for all z.
By Cauchy Integral Formula,
Z
f (z)
f (n) (0)
1
=
dz
n!
2i |z|=R z n+1
for all n and R > 0. Since |f (z)| |z| + 1,


f (z) |z| + 1
R+1


z n+1 |z|n+1 = Rn+1
1

for |z| = R. Therefore,



 

Z
1

f
(z)
R
+
1
R+1
1

(2R) =
dz
.
2i
n+1
n+1
2
R
Rn
|z|=R z
And since limR (R + 1)/Rn = 0 for n 2,
Z
1
f (z)
lim
dz = 0
R 2i |z|=R z n+1
and hence f (n) (0) = 0 for all n 2.
And since limR (R + 1)/Rn = 1 for n = 1,


Z


f
(z)
1
1
lim
dz

R 2i
z2
|z|=R

and hence |f 0 (0)| 1. Therefore,


f (z) = f (0) + f 0 (0)z = az + b
with |a| = |f 0 (0)| 1.
Finally, by |az + b| |z| + 1, we obtain that |b| 1 by setting
z = 0.

(3) Let
z3
f (z) = 2
z 5z + 4
Find the Laurent series of f (z) in each of the following domains:
(a) 1 < |z| < 4
(b) 1 < |z 2| < 2
Solution. We write f (z) as a sum of partial fractions:
z3
1
64
=z+5
+
.
2
z 5z + 4
3(z 1) 3(z 4)
For 1 < |z| < 4,
 
z3
1
1
16
1
=z+5

2
z 5z + 4
3z 1 1/z
3 1 z/4

1 X 1
16 X z n
=z+5

3z n=0 z n
3 n=0 4n
=
=

X
X
1
1 1
zn

3z n 3 3
3 4n2
n=1
n=2

X
n=0

X zn
1

3z n1 n=2 3 4n2

For 1 < |z 2| < 2,


z3
1
1
64
1
= (z 2) + 7
+
2
z 5z + 4
3 (z 2) + 1
3 (z 2) 2
1
32
1
1

= (z 2) + 7
3(z 2) 1 + 1/(z 2)
3 1 (z 2)/2

X (1)n
X (z 2)n
= (z 2) + 7

3(z 2)n+1 n=0 3 2n5


n=0
=

X
X
(1)n
(z 2)n
11 13

(z

2)

3(z 2)n
3
3
3 2n5
n=1
n=2

(4) Do the following:




+i .
(a) Find tan
4
Solution.


ei(/4+i) ei(/4+i)
tan
+ i = i i(/4+i)
4
e
+ ei(/4+i)
1
e (cos(/4) + i sin(/4)) e(cos(/4) i sin(/4))
= i 1
e (cos(/4) + i sin(/4)) e(cos(/4) i sin(/4))
(e + e1 ) + i(e e1 )
=
(e + e1 ) i(e e1 )
2e2
e4 1
= 4
+ 4
i
e +1 e +1
(b) Find the first three terms (i.e. up to z 2 ) of the Taylor series
of tan z at z = 0 and also its radius of convergence.
Solution. Let f (z) = tan z. Then
f (z) =

X
f (n) (0)
n=0

n!

zn

for |z| < R, where f (z) is analytic in |z| < R. Since tan z
is odd, f (n) (0) = 0 for n even. And since (tan z)0 = sec2 z,
f 0 (0) = 1. Therefore, the first three terms are
0 + z + 0z 2 = z
The radius of convergence of the Taylor series is the largest
R such that tan z is analytic in |z| < R. Since tan z is
analytic in {z 6= n + /2 : n integers}, the largest R with
this property is /2. So the radius of convergence is /2.

(c) Show that


| tan(z)|2 1 +

1
cos2 (x)

| tan(z)|2 1 +

1
sinh2 (y)

and

for all z C, where x = Re(z) and y = Im(z). Here we


take the right hand sides to be if cos x = 0 or sinh y = 0.
Proof. We know that tan2 (z) = sec2 (z) 1 and
| cos(z)|2 = | cos(x + yi)|2 = | cos(x) cos(yi) sin(x) sin(yi)|2
= | cos(x) cosh(y) i sin(x) sinh(y)|2
= cos2 x cosh2 y + sin2 x sinh2 y
= cos2 x(1 + sinh2 y) + sin2 x sinh2 y
= cos2 x + (cos2 x + sin2 x) sinh2 y = (cos x)2 + (sinh y)2 .
Therefore,




1
| tan(z)|2 = 2
1
cos (z)
1
1
=1+
.
1+
2
2
| cos(z)|
(cos x) + (sinh y)2
And since cos2 (x) 0 and sinh2 (y) 0,
| tan(z)|2 1 +

1
cos2 (x)

and
| tan(z)|2 1 +

1
.
sinh2 (y)


(d) Let CN be the boundary of the square


{|x| N , |y| N },
where N is a positive integer. Show that
Z
tan(z)
lim
dz = 0.
N C
z2
N

Proof. When x = N , |z| N and


| tan z|2 1 +

1
= 2.
cos2 (x)

When y = N , |z| N and


| tan z|2 1 +

1
1
=1+
< 2.
2
2
sinh (y)
sinh (N )

Therefore,



tan(z)
2


z2 N 22
for z CN . Consequently,
Z


CN


tan(z)
8 2
2
dz 2 2 (8N ) =
.
z2
N
N

And since limN 8 2/(N ) = 0,


Z
lim

CN

tan(z)
dz = 0.
z2


(5) Compute the integral


Z

x sin x
dx.
(x2 + 1)2

Solution. Obviously,
Z
0

Z
x sin x
1 x sin x
dxdx =
dx
(x2 + 1)2
2 (x2 + 1)2
Z

1
zeiz
dz
= Im
2
2
2
(z + 1)


Z R
1
zeiz
= Im lim
dz
R R (z 2 + 1)2
2

We integrate along the closed contour going from R to R and


then the semicircle CR = {|z| = R, Im(z) 0} counterclockwise. Then
Z R
Z
zeiz
zeiz
dz +
dz
2
2
2
2
R (z + 1)
CR (z + 1)
0

zeiz
zeiz

= 2i Resz=i 2
= 2i

2
2
(z + 1)
(z + i)
z=i

 iz
e + izeiz
2zeiz
i
= 2i

=
(z + i)2
(z + i)3 z=i 2e
by Cauchy Integral Theorem.
For z on CR , |eiz | = |ey | 1, |z 2 + 1| |z|2 1 = R2 1
and hence


iz


R
ze

z
(z 2 + 1)2 (R2 1)2
for z CR . Therefore,
Z

iz


ze
R2


dz
.

(z 2 + 1)2 (R2 1)2
CR

And since
R2
= 0,
R (R2 1)2
lim

we conclude that
Z
lim

CR

zeiz
dz = 0.
(z 2 + 1)2

Thus,
Z

lim

and
Z
0

zeiz
i
dz
=
(z 2 + 1)2
2e

x sin x

=
.
(x2 + 1)2
4e

(6) For each of the following complex functions, do the following:


find all its singularities in C;
write the principal part of the function at each singularity;
for each singularity, determine whether it is a pole, a removable singularity, or an essential singularity;
compute the residue of the function at each singularity.

1
(cos z)2
Solution. The function has singularities at {cos z = 0} =
{z = k + /2 : k integers}. At z = k + /2, we let
w = z k /2 and then

(a) f (z) =

1
1
=
=
(cos z)2
(sin w)2
1
= 2
w
=

1
w2

1
w2

n=0

!1

(2n + 1)!
!1

X
(1)n w2n
n=0

1 X
= 2
w m=0

X
(1)n w2n+1

1+

(2n + 1)!

X
(1)n+1 w2n
n=1

X
n=1

!1

(2n + 1)!
(1)n+1 w2n
(2n + 1)!
!

!m

an w n .

n=2

So the principal part at k + /2 is

1
,
(z k /2)2

the function has a pole of order 2 at k + /2 and

Resz=k+/2 f (z) = 0.

 
1
(b) f (z) = (1 z ) exp
z
3

Solution. The function has a singularity at 0 where


 

X
1
1
3
3
(1 z ) exp
= (1 z )
z
(n!)z n
n=0
=

X
n=0

=1+

X
1
1

n
(n!)z
(n!)z n3
n=0

X
n=1

X
1
1
z 1
3
2
+ )

(z
+
z
+
(n!)z n n=4 (n!)z n3
2 6

X
z 5 X 1
1
+ +

n
2 6 n=1 (n!)z
(n + 3)!z n
n=1


1
z 5 X 1
3
2

z n .
= z z + +
2 6 n=1 n! (n + 3)!

= z 3 z 2

So the principal part is




X
1
1

z n ,
n!
(n
+
3)!
n=1
the function has an essential singularity at 0 and
1
23
1
Resz=0 f (z) = = .
1! 4!
24
sin z
(c) f (z) = 2010
z
Solution. The function has a singularity at z = 0 where

sin z
1 X (1)n z 2n+1
= 2010
z 2010
z
(2n + 1)!
n=0
=

X
(1)n z 2n2009
n=0

(2n + 1)!

1004
X
(1)n z 2n2009
n=0

(2n + 1)!

X
(1)n z 2n2009
+
(2n + 1)!
n=1005

So the principal part is


1004
X
(1)n z 2n2009
n=0

(2n + 1)!

the function has a pole of order 2009 at 0 and


(1)1004
1
Resz=0 f (z) =
=
.
(2(1004) + 1)!
2009!

ez
1 z2
Solution. The function has two singularities at 1 and 1.
At z = 1,
 z 
e
ez
1
=
2
1z
z+1 1z
!

e1 X
1
+
an (z + 1)n
=
z+1
2
n=1
!

X
1
=
+
an (z + 1)n1 .
2e(z + 1) n=1

(d) f (z) =

So the principal part at 1 is


1
,
2e(z + 1)
the function has a simple pole at 1 and
1
Resz=1 f (z) = .
2e
At z = 1,
 z 
ez
1
e
=
2
1z
z1 z+1
!

1
e X
an (z 1)n
+
=
z 1 2 n=1

X
e
=

an (z 1)n1 .
2(z 1) n=1
So the principal part at 1 is
e

2(z 1)
the function has a simple pole at 1 and
e
Resz=1 f (z) = .
2

10

(7) Compute the following contour integrals.


(a)
Z
exp(sin z)dz,
C

where C is the ellipse 2x2 + y 2 = 1 oriented counterclockwise.


Solution. Since f (z) = ez and g(z) = sin z are entire,
f (g(z))R = exp(sin z) is entire. And since C is a closed
curve, C exp(sin z)dz = 0 by Cauchy Integral Theorem.
(b)
z 2011
dz,
2011 + z 2010 + z 2009 + 1
C z
where C is the circle |z| = 2 oriented counter-clockwise.
Solution. We first show that all zeroes of z 2011 + z 2010 +
z 2009 + 1 lie in |z| < 2. Otherwise, suppose that z 2011 +
z 2010 + z 2009 + 1 = 0 for some |z| 2. Then 1 + z 1 + z 2 +
z 2011 = 0. But
1
1
1
|1 + z 1 + z 2 + z 2011 | 1
2 2011
|z| |z|
|z|
1
1
1
1 2 2011 > 0
2 2
2
for |z| 2. Contradiction. So all zeroes of z 2011 + z 2010 +
z 2009 + 1 lie in |z| < 2. Therefore, z 2011 /(z 2011 + z 2010 +
z 2009 + 1) is analytic in |z| 2. It follows that
Z
z 2011
dz
2011 + z 2010 + z 2009 + 1
C z
z 2011
= 2i Resz= 2011
z
+ z 2010 + z 2009 + 1


1
z 2011
= 2i Resz=0 2
z
z 2011 + z 2010 + z 2009 + 1
1
= 2i Resz=0 2
z (1 + z + z 2 + z 2011 )
0


1

= 2i
= 2i.
1 + z + z 2 + z 2011
Z

z=0